Additional surgical procedures and perioperative morbidity in post-chemotherapy retroperitoneal lymph node dissection for metastatic testicular cancer in two intermediate volume hospitals - Blok, Joost M. (World J Urol, 2020)
PURPOSE: To evaluate the perioperative morbidity of PC-RPLND in two intermediate volume centers and to identify predictors of high morbidity. METHODS: Retrospective analysis of 124 patients treated with open PC-RPLND at two tertiary referral centers between 2001 and 2018. Perioperative morbidity was determined by analyzing additional surgical procedures, intra-operative blood loss, and postoperative complications. RESULTS: An additional procedure was necessary for 33 patients (26.6%). The risk was higher in patients with IGCCCG intermediate/poor prognosis (OR 3.56; 95% CI 1.33–9.52) and residual tumor size > 5 cm (OR 3.53; 95% CI 1.39–8.93). Blood loss was higher in patients with IGCCCG intermediate/poor prognosis (β = 0.177; p = 0.029), large residual tumor (β = 0.570; p < 0.001), an additional intervention (β = 0.342; p < 0.001) and teratoma on retroperitoneal histology (β = − 0.19; p = 0.014). Thirty-one patients had a postoperative complication Clavien-Dindo Grade ≥ 2 (25.0%). Complication risk was highest in patients undergoing an additional intervention (OR 3.46; 95% CI 1.03–11.60; p = 0.044). CONCLUSIONS: The rate of additional interventions in our series is comparable to what has been reported in high-volume centers. IGCCCG intermediate/poor prognosis patients with high-volume disease and patients undergoing an additional surgical procedure can be classified as high-risk patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00345-020-03229-5) contains supplementary material, which is available to authorized users.